Computer Generation Of Malay Sentences. - Tang, Enya Kong; Guo, Cheng Ming; Ahmad, Jumiya (Universiti Sains Malaysia, 2005)
In this project, we have successfully developed a sentence generator for Malay to be used in an Example-Based Machine translation (EBMT) system for English-Malay translation. Our approach is an example-based approach which relies sorely on example translations kept in a Bilingual Knowledge Bank (BKB). In our approach, a flexible annotation schema called Structured String-Tree Correspondence (SSTC) is used to annotate both the source and target sentences of a translation pair.